Nonlinearities in the EU sovereign debt crisis - Ferreira, N. B.; Oliveira, M.M. (International work-conference on Time Series, 2014)
Sights of sovereign debt crisis spread among financial players started in late 2009 as a result of the rising private and government debt levels worldwide. In 2010 news developments concerning Spain and Italy lead European nations to implement several financial support measures such as the European Financial Stability Facility. In an established crisis context, it was searched for evidence of nonlinearities, structural breaks and cointegration between interest rates and stock market prices in order to evaluate the impact effect analysis of the European markets contamination by sovereign debt. Four European markets under stress were examined using the United States of America as benchmark. It was found evidence in the crisis regime especially for Portugal, obtaining the greatest nonlinear threshold adjustment between interest rates and stock market returns. Moreover, significant structural breaks were found at the end of 2010 and the null hypothesis of no cointegration was consistently rejected.